Prototype Monitoring Sistem Kontrol Air Condition (AC) Diruang Rawat Inap Rumah Sakit Dengan Sensor Suhu Berbasis Raspberry Pi - Fadilla, Nuri; Nasir, Muhammad; Hidayat, Hari Toha (Jurnal Teknologi Rekayasa Informasi dan Komputer, 2022)
Each hospital has a room which uses air conditioning as an additional facility for patient comfort. From observations sofar, there is often an imbalance between the number of patients and nurses (paramedics), especially in the nursing service divisionwho is on duty 24 hours to monitor the condition of inpatients one by one in the room. This led to the motivation to create an airconditioner (AC) control system with a raspberry pi-based temperature sensor remotely via a monitor or smartphone with a webpage as the user interface. The implementation of this research followed the steps of remote control. The Wifi network is used as aliaison, and the Rasberry Pi is used as a data control device sent by Arduino where the DHT11 sensor reads the temperature in theroom which is sent to Arduino. The Rasberry Pi has installed the Apache web server, which allows it to be accessed from a webbrowser on the monitor or smartphone. From the test, the longest distance between the smartphone and the Rasberry Pi is 24 meters.All buttons on the web page have worked according to their function. The success rate is up to 80% on 30 tests at a distance of 30meters. Testing to determine the temperature of the cold room uses the ice vapor method so that the room temperature test resultsobtained reach 18 ° C. Testing to find out the room temperature is hot, using a heating method such as a hairdryer so that the roomtemperature test results obtained reach 31 ° C. To test the temperature comparison, a digital thermometer is used as a comparisonwith the results obtained between the module and the digital thermometer that the measurement results with the two tools do nothave a significant difference in temperature and humidity. keywords: AC,Sensor DHT11,Arduino,Rasberry Pi, IoT,Web.